La Tertulia; Buscando la reconexión entre la comunidad caleña y la cultura del arte : diseño de experiencia para el museo La Tertulia. (2022)
Tomake La Tertulia Museum closer to its community, enhancing their bond and this way promoting the art culture in the city. It is expected that in the long run, this solution can make a positive impact for the museum, increasing the participation of the community in its activities and facilitating the education in contemporary art related topics.